Discourse on Islamic Reformism in Colonial Malaya: a preliminary evaluation of selected literature - Zakariya, Hafiz (2011)
The age of imperialism, which stretched from the second half of nineteenth to the first half of twentieth centuries, engulfed almost every Muslim country. Anguished by European domination of the Muslim world, many Muslims doubted the supremacy of Islamic civilization, and at the same time are impressed by the advancement of the West. They are confronted by the dilemma of being able to emulate the West without compromising their religious principles. Muslims’ responses to colonialism varied from total rejection to blind imitation of the West. Another type of Muslim’s response attempted to bridge the gap between total rejection and blind imitation of the West. This attitude as epitomized by the ideas of Jamal al-Din al-Afghani and Muhammad ‘Abduh espoused a simultaneous admiration and rejection of the West. It emerged in the second half of the 19th century to revitalize Muslim conditions by focusing on its compatibility with modernity. Most studies on Islamic reformism have privileged the “central Islamic lands” at the expense of its “periphery” (Reid, 1993). As a result, comparatively, the development of Islamic reformism in Malaya (Malaysia) remains a marginal topic. This paper, thus, attempts to examine selected scholarly works on Islamic reformism in Malaya. In so doing, it will trace the intellectual progression of the field, including major debates, achievements and inadequacies.